제주지역 성인의 인구사회학적 특성과 비만에 따른 영양 및 식품섭취 상태 - 함현지(Hyunji Ham); 고한빈(Hanbin Ko); 김수민(Sumin Kim); 장유정(Youjeong Jang); 변종석(Jong-Seok Byun); 제갈윤석(Yoonsuk Jekal); 채인숙(Insuk Chai); 하경호(Kyungho Ha) (Journal of nutrition and health, 2024)
Purpose: This study evaluated the nutrition and food intake status among adults in Jeju, Republic of Korea, based on their sociodemographic characteristics and obesity. Methods: Nine hundred and forty-nine adults aged 19 years or older were included based on the 2022 Jeju Nutrition and Physical Activity Survey data. A dietary assessment was conducted using a one-day, 24-hour recall method, and the nutrition status was evaluated using the 2020 Dietary Reference Intakes for Koreans. The sociodemographic status included sex, age, education, and household income, and obesity was defined as a body mass index (BMI) of ≥ 25 kg/m2 . Results: The mean age of the subjects was 49.8 years, and the overall prevalence of obesity was 48.4% (59.5% for males and 37.2% for females). The top three insufficient nutrients consumed at less than the estimated average requirement were calcium (77.7%), vitamin A (77.3%), and vitamin C (61.3%), while 40.9% of the subjects consumed fat as more than 30% of their total energy intake. The sodium intake was approximately 1.5 times higher than the chronic disease risk reduction intake level. In terms of food groups, the participants consumed more meat (148.2 g/day), seafood (69.0 g/day), potatoes, and starches (41.6 g/day) but consumed fewer vegetables (214.3 g/day) and less dairy (62.0 g/day) than Korean adults. The nutritional status and food intake patterns differed by the sociodemographic status. In addition, the obese group consumed more poultry and beverages than the non-obese group (p < 0.05 for all). Conclusion: Adults in Jeju under-consume essential nutrients while over-consuming certain nutrients, such as fat and sodium. The nutritional status also varied according to the sociodemographic characteristics. These findings suggest that sociodemographic factors should be considered carefully when developing nutritional policies and programs to improve the nutritional status and address obesity among adults in Jeju. KCI Citation Count: 0